Pelatihan Pembuatan Lembar Kerja Peserta Didik (LKPD) Berdiferensiasi bagi Guru TK di Kabupaten Banyuasin - Suningsih, Taruni; Rukiyah, Rukiyah; Akbari, Akbari; Herdady, Syarifah Aliyah; Salsabillah, Asy-Syifa; Anggriyani, Putri Rizky (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Differentiated means related to differences. In the world of education, it is interpreted as learning that is tailored to the needs, potential, and interests of students. Differentiated learning is part of the Merdeka Curriculum that kindergarten teachers need to implement to create learning equality for all students. One of the applications is through the use of Worksheets (LKPD) in differentiated learning. This training aims to provide kindergarten teachers in Banyuasin Regency with the knowledge and skills to make worksheets in differentiated learning that are varied and interactive. Method: This training consists of material presentation, mentoring, and evaluation. This activity was carried out face-to-face (offline) and continued with virtual (online). Data collection techniques used tests and questionnaires, while data analysis techniques were descriptive quantitative. This activity involved 20 kindergarten teachers in Banyuasin Regency. Results: the activity showed an increase in kindergarten teachers' knowledge about differentiated worksheets. The average pre-test score of 56.5 increased to 91.25 in the post-test, with an increase of 35 points and an N-Gain value reaching 80.11% which is considered effective. The product of this activity is a differentiated worksheet that has been registered in Intellectual Property Rights (HAKI). Conclusion: This activity can increase the knowledge and skills of kindergarten teachers in Banyuasin Regency in making differentiated worksheet. This activity received a positive response from teachers as training participants.